Analisis Kemaslahatan pada Peraturan Pemerintah Republik Indonesia Nomor 10 Tahun 1983 Tentang Izin Poligami - Af’idaa, Fidaa; Nursobah, Achmad; Abqori, Najih (CV. ULIL ALBAB CORP, 2025)
This study analyzes Government Regulation No. 10 of 1983 concerning the practice of polygamy for Civil Servants (PNS) from the perspective of Islamic law, particularly through the approaches of maslahah and maqâsid al-syar'iyyah. The regulation aims to maintain the welfare of individuals, families, and society by establishing strict requirements, including the consent of the first wife and financial capability. The analysis shows that Government Regulation No. 10 of 1983 not only serves as an administrative instrument but also aligns with the principles of justice found in the Qur'an and Sunnah. Furthermore, this regulation contributes to social stability and protects the rights of women and children. Overall, Government Regulation No. 10 of 1983 supports a higher maslahah by creating a balance between individual rights and social justice.